Odpowiedź :
Odpowiedź:
3x² + 2 = 1 - 4x
3x² + 4x + 2 - 1 = 0
3x² + 4x + 1 = 0
a = 3 , b = 4 . c = 1
Δ = b² - 4ac = 4² - 4 * 3 * 1 = 16 - 12 = 4
√Δ = √4 = 2
x₁ = ( - b - √Δ)/2a = ( - 4 - 2)/6 = - 6/6 = - 1
x₂ = ( - b + √Δ)/2a = (- 4 + 2)/6 = - 2/6 = - 1/3
Odp: C
Odpowiedź:
3x² +2 = 1 -4x
x= -3
3* 9 +2= 1- 4* (-3)
Liczba - 3 nie spełnia równania
x= 1
3* 1² +2 = 1- 4*1
3+2= 1-4
Liczba 1 nie spełnia równania
x=1/3
3* (1/3)²+2 = 1 - 4 *(1/3)²
3*1/9 +2= 1- 4 *1/3)
3/9+2= 1-4/3
2 i 1/3 =1 - 1 i 1/3
Liczba 1/3 nie spełnia równania
Odp. C
x= - 1/3)
3* (-1/3)² +2= 1- 4* (-1/3)
3*1/9 +2= 1 +4/3
3/9 +2= 1 +1 i 1/3
2 i 1/3= 2 i 1/3
L=P
Liczba -1/3 spełnia równanie.
Szczegółowe wyjaśnienie: